The 3rd Alternative : Solving Life's Most Difficult Problems - Covey, Stephen R. (London Simon & Schuster, 2011)
Outlines a breakthrough approach to conflict resolution and creative problem solving that draws on the techniques of thinkers from a broad range of disciplines to explain how to incorporate diverse viewpoints for win-win solutions.
Include Index
Keywords: Problem solving -- Change (Psychology) -- Interpersonal conflict